The Effect of Realistic Mathematics Education Model Assisted by Puzzle on Mathematical Problem-Solving Skills for Grade III Students - Antono, Dellia Putri; Yustiana, Sari; Kusumadewi, Rida Fironika (Al-Aulad: Journal of Islamic Primary Education, 2024)
The ability to solve mathematical problems for class III students at SDN 1 Tunjungharjo using the realistic mathematics education (RME) model assisted by puzzle media is the focus of this research. Use of quantitative methods with a pre-experimental one group pretest and posttest design to obtain research data. A systematic sampling procedure was used to select the sample, with 37 students serving as the research sample from a total population of 40 students. The findings of this research show that students understand the indicators of problem solving: reading and understanding the problem, exploring the problem, choosing a solution strategy, looking for answers, and checking again. The results of the data analysis carried out show that there is an influence of the realistic mathematics education model assisted by puzzle media on the mathematical problem solving abilities of class III students. This is shown by the results of the paired sample t-test where Lower has a negative value with a gain of -53.279 and Upper has a negative value with a gain of -44.018 and a Sig value. (2-tailed) 0.000 < 0.05 which means Ho is rejected and H1 is accepted. Apart from that, the gain test results showed an increase in the medium category with a score of 0.674.